Measurement of 14N quadrupole couplings in biomolecular solids using indirect-detection 14N solid-state NMR with DNP. Issue 89 (26th October 2017) - Jarvis, J. A.; Haies, I.; Lelli, M.; Rossini, A. J.; Kuprov, I.; Carravetta, M.; Williamson, P. T. F.
Abstract : Insights into protein structure through the determination of 14 N quadrupolar interactions using magic-angle spinning dynamic nuclear polarization NMR. Abstract : The quadrupolar interaction experienced by the spin-1 14 N nucleus is known to be extremely sensitive to local structure and dynamics. Furthermore, the 14 N isotope is 99.6% naturally abundant, making it an attractive target for characterisation of nitrogen-rich biological molecules by solid-state NMR. In this study, dynamic nuclear polarization (DNP) is used in conjunction with indirect 14 N detected solid-state NMR experiments to simultaneously characterise the quadrupolar interaction at multiple 14 N sites in the backbone of the microcrystalline protein, GB3. Considerable variation in the quadrupolar interaction (>700 kHz) is observed throughout the protein backbone. The distribution in quadrupolar interactions observed reports on the variation in local backbone conformation and subtle differences in hydrogen-bonding; demonstrating a new route to the structural and dynamic analysis of biomolecules.